PROSPEK PENGEMBANGAN MESIN TANAM PINDAH BIBIT PADI DALAM RANGKA MENGATASI KELANGKAAN TENAGA KERJA TANAM BIBIT PADI - Suhendrata, Tota (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
Farm  labor  scarcity  could  delay  planting  time  and  not  simultaneously planting,  so  that  it  has  influence  to  the  index  of  rice  planting,  OPT’s  disturbance which eventually affects to rice production. This condition requires the presence of the rice seedling  planting machines, one of those is rice transplanter. This research aims to find out the technical and financial feasibility of rice transplanter viewed from business  services  and  farming  utilizing  rice  transplanter.  The  application  of  rice transplanter,  was carried out in Somomorodukuh village, Plupuh sub district, Sragen district  in  MT-1  2012/2013.  The  collected  data  includes  the  performance  and  the operational  cost  of  rice  transplanter,  paddy  productivity  as  well  as  the  cost  of  rice farming’s.  For  finding  out  the  financial  feasibility  of  rice  transplanter’s  business services, it was used Net Present Value (NPV), Internal Rate of Return (IRR), BenefitCost Ratio (B/C) and Pay Back Periode (PP) analysis. To find out the feasibility of planting technology change, it was used Losses and Gains analysis. The result shows that (1) the use of rice transplanter can help solve the problem of farm labor scarcity, (2) the business service of rice transplanter is feasible to run and to develop widely with NPV=Rp22.4 millions, IRR=59.59%, B/C=1.26 and PP=2.42 years, (3) planting using rice transplanter can increase income as much as  Rp2,690,000/ha/season with marginal B/C as much as 23.42, so that it’s worth to widely be implemented, and (4) the use of rice transplanter can benefit both sides, namely the owner and the farmer.